Implementation of Integrative Arabic Grammar (Nahwu & Sharaf) Curriculum in Islamic Boarding School - Ardiansyah, Ade Arip; Muhammad, Azhar (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2020)
<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">Learning Nahwu & Sharaf is considered a frightening subject by students in Islamic boarding schools and informal Islamic boarding schools. One of the reasons is that the institution's existing curriculum has not been planned and presented correctly. One of the institutions with an integrative curriculum to teach Nahwu & Sharaf subjects considered acceptable is the Darul Uluum Islamic Boarding School.<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">This study aimed to describe Nahwu <span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">& Sharaf <span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">curriculum development concepts and models at Daarul Uluum Islamic boarding school at <span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">M<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">ajalengka supporting and inhibiting implementing the curriculum. The method used in this study was qualitative research.<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> D<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">ata collection used interviews, the teacher's approach to teaching Nahwu & Sh<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">a<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">r<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">a<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">f<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">,<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> and the Islamic boarding school syllabus.<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">The results showed that Nahwu <span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">& Sharaf <span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">curriculum development model was a central de-central, which combined two administrative approaches and the grassroots approach. The supporting factors were: 1) Motivation of leaders of Islamic boarding school<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">; <span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">2) Commitments of leaders of Islamic boarding school<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">to develop curriculum, 3) Professional competence of Nahwu <span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">& Sharaf <span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">teachers, and 4) Input of students who have an initial understanding of the material to be obtainable. The inhibiting factors were: 1) the lack of individual funding allocations; 2) the teacher has not been able to properly teach students the material in Nahwu & Sharaf syllabus; 3) the unequal ability of teachers to teach in class Nahwu <span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; color: black; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">& Sharaf <span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">subjects; and 4) <span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">students feel bored while studying in class<span style="font-size: 8.0pt; line-height: 107%; font-family: 'Tahoma',sans-serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]-->